Novel assay to measure chromosome instability identifies Punica granatum extract that elevates CIN and has a potential for tumor- suppressing therapies - Goncharov, Nikolay V.; Kovalskaia, Valeria A.; Romanishin, Alexander O.; Shved, Nikita A.; Belousov, Andrei S.; Tiasto, Vladlena S.; Gulaia, Valeriia S.; Neergheen, Vidushi S.; Rummun, Nawraj; Liskovykh, Mikhail; Larionov, Vladimir; Kouprina, Natalay; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Human artificial chromosomes (HACs) have provided a useful tool to study kinetochore structure and function, gene delivery, and gene expression. The HAC propagates and segregates properly in the cells. Recently, we have developed an experimental high-throughput imaging (HTI) HAC-based assay that allows the identification of genes whose depletion leads to chromosome instability (CIN). The HAC carries a GFP transgene that facilitates quantitative measurement of CIN. The loss of HAC/GFP may be measured by flow cytometry or fluorescence scanning microscope. Therefore, CIN rate can be measured by counting the proportion of fluorescent cells. Here, the HAC/GFP-based assay has been adapted to screen anticancer compounds for possible induction or elevation of CIN. We analyzed 24 cytotoxic plant extracts. Punica granatum leaf extract (PLE) indeed sharply increases CIN rate in HT1080 fibrosarcoma cells. PLE treatment leads to cell cycle arrest, reduction of mitotic index, and the increased numbers of micronuclei (MNi) and nucleoplasmic bridges (NPBs). PLE-mediated increased CIN correlates with the induction of double-stranded breaks (DSBs). We infer that the PLE extract contains a component(s) that elevate CIN, making it a candidate for further study as a potential cancer treatment. The data also provide a proof of principle for the utility of the HAC/GFP-based system in screening for natural products and other compounds that elevate CIN in cancer cells.